KAFURUI SEBAGAI PENGOBATAN ALTERNATIF PATAH TULANG PADA MASYARAKAT MUNA DI DESA LIANGKABORI - Nur Kisa; Rahmat Sewa Suraya (KABANTI : Jurnal Kerabat Antropologi, 2023)
Kafurui (massage) is a traditional healing or health therapy method, by applying pressure to the body either in a structured, unstructured, sedentary or moving place by applying pressure and done manually.This study aims to find out and describe the reasons why people choose Kafurui as an alternative treatment for fractures and to find out the process carried out by shamans in treating fracture patients in Liangkabori Village.The data collection technique used in this research is field research technique using two methods, namely involved observation and in-depth interviews. The results of this study indicate that people choose Kafurui as an alternative treatment due to several factors, namely habit factors, economic factors, experience factors and easy-to-reach factors. The process of treating fracture patients depends on the type of fracture, the process of treating mild fractures, the shaman touches the broken part while saying two sentences of shahada after which the patient begins to be sequenced (kafurui). Severe fractures that are accompanied by wounds are not massaged at the beginning of treatment, but only blown with mantras, until the wounds begin to heal, then the sequencing process begins. The first step taken by the shaman is to reposition the bones or rearrange the bones that have been crushed so that they can return to their previous arrangement by sequencing. In this sugar cane fracture, since the patient came for treatment, the sequencing process has begun because there is no wound so that infection will not occur.